Expression of microRNAs in bovine and human pre-implantation embryo culture media - Kropp, Jenna; Salih, Sana M.; Khatib, Hasan (Frontiers in Genetics, 2014)
MicroRNAs (miRNA) are short non-coding RNAs which act to regulate expression of genes driving numerous cellular processes. These RNAs are secreted within exosomes from cells into the extracellular environment where they may act as signaling molecules. In addition, they are relatively stable and are specifically expressed in association to certain cancers making them strong candidates as biological markers. Moreover, miRNAs have been detected in body fluids including urine, milk, saliva, semen, and blood plasma. However, it is unknown whether they are secreted by embryonic cells into the culture media. Given that miRNAs are expressed throughout embryonic cellular divisions and embryonic genome activation, we hypothesized that they are secreted from the embryo into the extracellular environment and may play a role in the developmental competence of bovine embryos. To test this hypothesis, bovine embryos were cultured individually from day 5 to day 8 of development in an in vitro fertilization system and gene expression of 5 miRNAs was analyzed in both embryos and culture media. Differential miRNA gene expression was observed between embryos that developed to the blastocyst stage and those that failed to develop from the morula to blastocyst stage, deemed degenerate embryos. MiR-25, mir-302c, miR-196a2, and miR-181a expression was found to be higher in degenerate embryos compared to blastocyst embryos. Interestingly, these miRNAs were also found to be expressed in the culture media of both bovine and human pre-implantation embryos. Overall, our results show for the first time that miRNAs are secreted from pre-implantation embryos into culture media and that miRNA expression may correlate with developmental competence of the embryo. Expression of miRNAs in in vitro culture media could allow for the development of biological markers for selection of better quality embryos and for subsequent successful pregnancy.